The complete researcher : a practical guide for graduate students and early career professionals - Hook, Joshua N.; Davis, Don E.; Van Tongeren, Daryl R. (American Psychological Association, 2024)
"This book is designed to help psychology grad students and early career professionals develop skills to effectively work through the research process"--